The ameliorative effects of selected herbal extracts on glucose levels in albino mice induced with Mancozeb - S. RAZIA (International Journal of Pharma and Bio Sciences, 2019)
Pesticides were used to increase food production to meet the global requirement; however it causes adverse effects in humans and animals. One of the mostly used pesticides is Dithiocarbamate, a broad spectrum fungicide. Mancozeb is a fungicide of Ethylene Bis-Dithiocarbamate (EBDCs) group. It is a widely used fungicide due to its reportedly low toxicity against diseases in field crops and is the most commonly used in Madhya Pradesh, India. However its breakdown product ethylene thiourea has toxic effect in number of experimental animals. The objective of the current study was to investigate the therapeutic effect of crude extracts of Aloe vera and Ocimum sanctum against mancozeb in Swiss albino mice. Two doses of mancozeb at 4.2 mg/kg/day and 6.7 mg/kg/day dissolved in distilled water were administered in albino mice for four weeks. The aqueous leaf extracts of Ocimum sanctum at 250 mg/kg/bw and Aloe vera at 400 mg/kg/bw was evaluated in these mancozeb intoxicated groups. In the mancozeb exposed group, significant decrease in blood glucose level was seen compared to control, while in the herbal treated groups the results showed significant increase in glucose level towards that of control. The healing and repair of the liver tissue with both the aqueous leaf extracts of A. vera and O. sanctum probably helped in the acceleration of glucose generation mechanism which may have contributed to the increase of glucose level in the treated mice. Thus, the current study indicates that mancozeb administered at very low doses produced significant detrimental effects on Swiss albino mice and the aqueous extracts of Aloe vera and Ocimum sanctum has therapeutic effect against it on the blood glucose level in albino mice.